Developing a national occupational health surveillance system in the United States. - Frazier, Todd M. (Scandinavian Journal of Work, Environment & Health, 1981)
The United States National Institute for Occupational Safety and Health (NIOSH) is developing a national information base for the identification of workplace hazards and for the detection of work-related disease, disability, or mortality. In the first national occupational hazard survey completed in 1974, surveyors observed more than 85,000 tradename products in a probability sample of 5,000 US workplaces. Manufacturers of these tradename products have given NIOSH information about the chemical ingredients in more than 60,000 products. Prior to this survey the ability to identify and inform workers of the potential hazards to which they were exposed was limited. The occupational health effect surveillance system is presently based on data obtained from three data systems, the national Health Interview Survey, the Social Security Administration Disability Award File and proportionate mortality ratio studies conducted by several states. Industry and associated disease rubrics identified by these data systems become topics for more intensive analysis culminating in brief reports called surveillance intelligence bulletins (SIBs). This paper gives an example of work in progress in developing an SIB concerned with accidents among loggers.
Keywords: accident; death; disability; disease; hazard; information system; logger; national occupational health surveillance system; national surveillance system; occupational health surveillance; occupational health surveillance system; surveillance system; tradename product; United States